(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
The fruits’ morphological peculiarities of 19 species from section Medium D.C. of genus Campanula L. in the flora of Ukraine were studied. The common features (base or medium aperture location) and specific ones (globose or inversely ovate capsules form, erect or pendent pedicles, dense, dispersed pubescens from rigid, soft hair or its absence) have been revealed.